Hukuman Mati Bagi Koruptor Perspektif Fikih Peradilan Islam - M. Arif Fatkhurrozi; Roudlotul Jannah (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study will discuss the death penalty for corruptors in the view of fiqh. Criminal sanctions that have not been fully effective given to corruptors, do not provide a deterrent effect, so that corruption cases in this country in particular still continue. This research is a qualitative research using fiqh perspective to reveal the punishment for corruptors. As a result, corruption is not definitively known in fiqh studies, but the substance of the actions categorised as corruption has similarities with the forms of jarimah that cause the law of had and even qishah if it is related to the rights of the general public. There are meanings of sariqah, ghulul, risywah and khianat in corrupt practices against the law. Sanctions for acts of corruption are takzir so that the death penalty can be applied using the legal argument of maslahah al mursalah.